Deep-sea faunal provinces and their inferred environments in the Indian Ocean based on distribution of Recent benthic foraminifera - De, Soma; Gupta, Anil K. (Palaeogeography Palaeoclimatology Palaeoecology, 2010)
Multivariate analysis was performed on percentages of 46 species of unstained deep-sea benthic foraminifera from 131 core-top to near-core-top samples (322-5013 m) from across the Indian Ocean. Faunal data are combined with GEOSECS geochemical data to investigate any relationship between benthic foraminifera (assemblages and species) and deep-sea properties. In general, benthic foraminifera show a good correlation to surface productivity, organic carbon flux to the sea floor, deep-sea oxygenation and, to a lesser extent, to bottom temperature, without correlation with the water depths. The foraminiferal census data combined with geochemical data has enabled the division of the Indian Ocean into two faunal provinces. Province A occupies the northwestern Indian Ocean (Arabian Sea region) where surface primary production has a major maximum during the summer monsoon season and a secondary maximum during winter monsoon season that leads to high organic flux to the seafloor, making the deep-sea one of the most oxygen-deficient regions in the world ocean, with a pronounced oxygen minimum zone (OMZ). This province is dominated by benthic foraminifera characteristic of low oxygen and high organic food flux including Uvigerina peregrina, Robulus nicobarensis, Bolivinita pseudopunctata, Bolivinita sp., Bulimina aculeata, Bulimina alazanensis, Ehrenbergina carinata and Cassidulina carinata. Province B covers southern, southeastern and eastern parts of the Indian Ocean and is dominated by Nuttallides umbonifera, Epistominella exigua, Globocassidulina subglobosa, Uvigerina proboscidea, Cibicides wuellerstorfi, Cassidulina laevigata, Pullenia bulloides, Pullenia osloensis, Pyrgo murrhina, Oridorsalis umbonatus, Gyroidinoides (=Gyroidina) soldanii and Gyroidinoides cf. gemma suggesting well-oxygenated, cold deep water with low (oligotrophic) and pulsed food supply. (C) 2010 Elsevier B.V. All rights reserved.
id: 1967; PT: J; UT: WOS:000278782400021